2018
DOI: 10.1080/02786826.2018.1430350
|View full text |Cite
|
Sign up to set email alerts
|

Measuring ultrafine aerosols by direct photoionization and charge capture in continuous flow

Abstract: Direct ultraviolet (UV) photoionization enables electrical charging of aerosol nanoparticles without relying on the collision of particles and ions. In this work, a low-strength electric field is applied during particle photoionization to capture charge as it is photoemitted from the particles in continuous flow, yielding a novel electrical current measurement. As in conventional photocharging-based measurement devices, a distinct electrical current from the remaining photocharged particles is also measured do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The particle size is varied by changing the flow rate of propane into the flame. Higher flow rates of propane would yield larger particles [40].…”
Section: Construction Of Soot Particle Generatormentioning
confidence: 99%
“…The particle size is varied by changing the flow rate of propane into the flame. Higher flow rates of propane would yield larger particles [40].…”
Section: Construction Of Soot Particle Generatormentioning
confidence: 99%
“…(which increases with the particles charging state q), and the material dependent exponent m. For example, the charging probability of NaCl aerosols is substantially lower than for carbonaceous species like soot, which basically enables material specific measurements [9]. The photoelectric charging efficiency is enhanced especially for particles smaller than 50 nm, and it was further shown by Nishida et al [9] that the sensor response of their photoelectric charger is proportional to the particles surface area…”
Section: Theory and Measurement Principlementioning
confidence: 99%
“…The electrons released via photoemission from particles in a carrier gas collide with neutral gas molecules, forming gaseous ions. It has been previously shown that under conditions where the recombination rate of ions with charged particles is not dominant, the total photoelectric activity generated over the total irradiation time (t irr ) can be measured by collecting the total current of photoemitted electrons (i e ), or the remaining positively charged particles (i o ) (Nishida et al, 2017(Nishida et al, , 2018. For polydispersed particle size distributions over a range of conditions, the contribution of each photoemission event to the net photoelectric current may be assumed to be independent (Nishida et al, 2019).…”
Section: Theorymentioning
confidence: 99%
“…Jung and Kittelson (2005) measured the size and composition-dependent responses of two unipolar charging-based instruments and one photoelectric instrument as a function of Fuchs surface area, which is directly proportional to the particle mobility diameter and measurement regime. Therefore, the mobility diameter may be used in the photoelectric charging equations by neglecting the effect of particle morphology (Nishida et al, 2018). However, total photoelectric yield, as measured by electrical current in Eqn 3, is proportional to the photoelectrically active surface, which can be conflated with geometric surface area or an equivalent surface area based on mobility measurements.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation